Comparison Between Familial Colorectal Cancer Type X and Lynch Syndrome: Molecular, Clinical, and Pathological Characteristics and Pedigrees - Xu, Yun; Li, Cong; Zhang, Yuqin; Guo, Tian’an; Zhu, Congcong; Xu, Ye; Liu, Fangqi (Frontiers in Oncology, 2020)
Abstract Objective: This study aimed to compare the molecular, clinical, and pathological characteristics and pedigrees of familial colorectal cancer type X (FCCXT) with those of Lynch syndrome (LS) to provide a theoretical basis for the management of FCCTX. Methods: Overall, 46 cases of FCCTX and 47 LS probands and affected families were enrolled between June 2008 and September 2018 for this study. Multigene cancer panel tests that included 139 genes were performed for all patients, and variants in each group were described. The clinical, pathological, and pedigree characteristics were also compared between the two groups. Results: In total, 42 variants were detected in 27 (58.7%) cases in the FCCTX group, with BRCA1, BRCA2, POLE, POLD1, ATR, and ATM being the most frequently mutated genes. The mean onset age of CRC was significantly older in the FCCTX group than in the LS group (53.57 ± 12.88 years vs. 44.36 ± 11.26 years, t = -9.204, p < 0.001). The proportion of patients with rectal cancer was also higher in the FCCTX group than in the LS group (43.5% (20/46) vs. 10.6% (5/47), 2 = 12.823, p = 0.005). Within a median follow-up time of 53.9 ± 37.0 months, the proportion of patients who developed metachronous CRC was significantly higher in the LS group than in the FCCTX group (34.0% (16/47) vs. 13.0% (6/46), 2 = 5.676, p = 0.017). When comparing pedigrees, older age of cancer onset and rectal cancer clustering were observed in the FCCTX families. A higher prevalence in male patients was also observed in the FCCTX families. Conclusions: FCCTX is an entity distinct from LS, but its genetic etiology remains unknown. A larger multigene panel would be recommended for determining the underlying pathogenic variants. Considering the pathology and moderate penetrance of the CRC link to FCCTX, less stringent surgical treatments and colonoscopy surveillance would be preferable. Rectum preference is a typical feature of FCCTX. Colonoscopy surveillance in FCCTX families could be less intensive, and more attention should be given to male members.